2005
DOI: 10.1634/stemcells.2004-0304
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression Profiling of Human Umbilical Cord Blood–Derived Mesenchymal Stem Cells by DNA Microarray

Abstract: Mesenchymal stem cells (MSCs) retain both self-renewal and multilineage differentiation capabilities. Despite wide therapeutic potential, many aspects of human MSCs, particularly the molecular parameters to define the stemness, remain largely unknown. Using high-density oligonucleotide microarrays, we obtained the differential gene expression profile between a fraction of mononuclear cells of human umbilical cord blood (UCB) and its MSC subpopulation. Of particular interest was a subset of 47 genes preferentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 34 publications
3
64
0
3
Order By: Relevance
“…The analysis of their gene expression profile reveals similarities to BM-MSCs (Jeong et al 2005), with an ability to differentiate into adipocytes, osteoblasts (Lee et al 2004), hepatocytes (Kang et al 2006) and neuronal-like cells (Hou et al 2003).…”
Section: Cord Derived Mesenchymal Stem Cellsmentioning
confidence: 99%
“…The analysis of their gene expression profile reveals similarities to BM-MSCs (Jeong et al 2005), with an ability to differentiate into adipocytes, osteoblasts (Lee et al 2004), hepatocytes (Kang et al 2006) and neuronal-like cells (Hou et al 2003).…”
Section: Cord Derived Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Fibroblast growth factor-4 and hepatocyte growth factor induce differentiation of human umbilical cord blood-derived mesenchymal stem cells into hepatocytes that they are similar to bone marrow-derived MSCs not only with respect to cellular properties and multilineage differentiation potential, but also with respect to their molecular context [19,20] . It was reported that HUCB-derived MSCs could differentiate into mesoderm cells such as osteoblasts, adipocytes [21] , neuron-like cells [19,22] , and cardiomyocytes [23,24] .…”
Section: The Extensive Characterization Of These Cells Has Revealedmentioning
confidence: 99%
“…Concentrations of AFP and albumin in the changed medium were determined by radioimmunoassay on d 4,8,12,16,20,24, and 28. Since there might be a very small amount of AFP and albumin in the changed medium, the medium was condensed 5 times by freeze drying before radioimmunoassay.…”
Section: Radioimmunoassaymentioning
confidence: 99%
“…Therefore, the elucidation of potential mechanisms is vital for the further development of stem cell therapy techniques and, ultimately, their translation to the bedside. A number of proposed mechanisms have been investigated in preclinical cerebral ischemia models, including the formation of new neuronal circuitry, reduced apoptosis, promotion of angiogenesis, neurogenesis, and other endogenous www.nature.com/aps Zhu Y et al Acta Pharmacologica Sinica npg repair processes [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%